2022
DOI: 10.1080/21655979.2022.2056824
|View full text |Cite
|
Sign up to set email alerts
|

The role of microRNA-4723-5p regulated by c-myc in triple-negative breast cancer

Abstract: The aim of this study was to investigate the expression of miRNA regulated by c-myc and its mechanism in three negative breast cancer (TNBC). We constructed MDA-MB-231 cell line with low expression of c-myc by lentivirus short hairpin RNA (shRNA), analyzed the miRNA expression profile of MDA-MB-231 cell line with different expression levels of c-myc by high-throughput sequencing technology, obtained differential miRNA by bioinformatics analysis and statistical analysis, and verified hsa-mir-4723-5p by Quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…Previous findings suggest that FUBP1 may play a role in the carcinogenesis process by relying on the c-Myc pathway [ 39 ]. Compared with the results of Jin et al [ 38 ]. This study further identified the important role of FUBP1 binding to c-Myc in colon cancer progression.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Previous findings suggest that FUBP1 may play a role in the carcinogenesis process by relying on the c-Myc pathway [ 39 ]. Compared with the results of Jin et al [ 38 ]. This study further identified the important role of FUBP1 binding to c-Myc in colon cancer progression.…”
Section: Discussionmentioning
confidence: 60%
“…Moreover, Ding et al [ 19 ] found that c-Myc was expressed in more than 75% of gliomas, and its high expression was also related to the low survival rate of human gliomas. Jin et al showed that c-Myc knockout could inhibit the occurrence and metastasis of triple negative breast cancer by reducing the expression of Hsa-mir-4723-5p [ 38 ]. Treating c-Myc-dependent tumors could be achieved by affecting the expression of FUBP1 [ 16 ].…”
Section: Discussionmentioning
confidence: 99%